Improving the light scattering efficiency of photoelectrode dye-sensitized solar cell through optimization of core-shell structure - Zaine, S.N.A. (2019)
Improving the capability to capture photon radiation by the photoelectrode film is one of the promising efforts in developing high performance dye-sensitized solar cell (DSC) through enhancing the light harvesting efficiency by the incorporation of light scattering centre. The scattering centre serves to extend the optical path length and improve the long-wavelength response of the DSC. This study aims to develop an optimum structure of micron-size SiO2 core and TiO2 nanoshell structure as light scattering centre for the photoelectrode film of DSC. MATLAB simulation of extinction efficiency based on Mie scattering theory estimated that the optimum size of light scatterer scattering size is in the range of 150â250 nm with shell thickness of about 10â45 nm. Integration of 15 SiO2-TiO2 core-shell (STCS) into the upper layer of double layers printed photoelectrode resulted in the highest short circuit current. Although the photoelectrode film embedded with STCS structure seems to have a significant reduction in the amount of anchored dye due to its low surface area, but its IPCE analysis shows better photocurrent response especially in the wavelength range of 400â650 nm. The enhancement is attributed to the effective light scattering of the STCS structure which is capable of extending the travel distance of the incidence photon thus increasing the amount of photon captured by the sensitized dye molecules. Besides, the embedded STCS structures also help in increasing the recombination resistance, reducing rate of electron recombination, hence improving the electron lifetime. Â© 2019 Elsevier Ltd